Red blood cell distribution width to albumin ratio and systemic immune-inflammatory index as predictors of mortality in severe pneumonia: A retrospective cohort analysis - Lijia Shao; Rui Gong; Lihong Shen (PLoS ONE, 2026)
Objective Severe pneumonia carries a high risk of mortality. There is a need for readily available prognostic biomarkers to improve risk stratification. This study evaluated the prognostic value of two novel composite indices, the red blood cell distribution width-to-albumin ratio (RAR) and the systemic immune-inflammation index (SII), in patients with severe pneumonia. Methods This retrospective cohort study extracted data from electronic medical records of 194 adult patients (age ≥ 18 years) with severe pneumonia (diagnosed per Chinese guidelines) admitted to Jinhua Hospital (January 2022 to December 2024). After screening 2,268 admissions, 194 patients with complete 24-hour data were classified into survivors (n = 147) and non-survivors (n = 47). Associations between RAR, SII, and in-hospital mortality were analyzed using multivariate logistic regression, receiver operating characteristic (ROC) curves, and Kaplan-Meier survival analysis. Results Compared with survivors, non-survivors had a significantly higher RAR (median: 0.44 vs. 0.37, p < 0.001) and SII (median: 2389 vs. 1870, p = 0.002). RAR was positively correlated with D-dimer ( r = 0.254, p < 0.001), and negatively correlated with uric acid (UA) ( r = −0.147, p = 0.042). SII was positively correlated with C-reactive protein (CRP) ( r = 0.150, p = 0.037) and interleukin-6 (IL-6) ( r = 0.188, p = 0.009). Advanced age ( OR =1.042; 95% CI :1.004–1.082; p = 0.030), high RAR ( OR =2.492; 95% CI :1.642–3.781; p < 0.001) and high SII ( OR =1.575; 95% CI :1.074–2.309; p = 0.036) were independent risk factors for death in patients with severe pneumonia. The ROC of RAR and SII for predicting death in patients with severe pneumonia was 0.722 and 0.652, respectively. Patients with RAR < 0.43 had a higher cumulative survival than patients with RAR ≥ 0.43 (85.6% [119/139] vs. 50.9% [28/55]; HR = 4.987; 95% CI : 2.592–9.593; p < 0.001); Patients with SII < 2120 had a higher cumulative survival than patients with SII ≥ 2120 (86.9% [93/107] vs. 62.1% [54/87]; HR = 2.745; 95% CI : 1.531–4.924; p < 0.001). Conclusions Elevated RAR and SII are significantly associated with an increased risk of in-hospital death in severe pneumonia patients. These indices may therefore serve as useful, readily available, and inexpensive prognostic tools.